Changes in Patient-Reported Symptoms Across Chemotherapy Cycles: A Prospective Cohort Study in an Outpatient Chemotherapy Clinic - Maria Lavdaniti; Ioanna Tsatsou; Anastasia Asimakopoulou; Antzouletta Kampitsi; Antonia Vasilopanagi; Mpara Ourania; Polixeni Liamopoulou; Theocharis I. Konstantinidis; George Tzavelas (Nursing Reports, 2026)
Background/Objectives: Cancer patients undergoing treatment experience a wide range of physical and psychological symptoms that significantly impact their quality of life. This study aimed to evaluate the occurrence and intensity of symptoms in cancer patients using the Edmonton Symptom Assessment System Revised (ESAS-R) during two distinct phases of treatment. Methods: A prospective cohort study with consecutive recruitment of eligible patients within a convenience sample was conducted in a tertiary public cancer hospital in Athens, Greece. The initial sample included 189 adult cancer patients assessed after the third chemotherapy cycle. Of these, 105 patients completed a second assessment after the final chemotherapy cycle and constituted the longitudinal follow-up sample. Symptom intensity was measured using the 10-item ESAS-R self-report tool. Results: The study population was predominantly female (77.2%), married (71.4%), and diagnosed with breast cancer (59.3%). Statistically significant changes between the two measurements (p < 0.05) were observed in pain, fatigue, and well-being. Total symptom burden scores remained relatively stable, slightly decreasing from 25.09 to 24.19. Age showed a consistent negative correlation with pain (p < 0.001) in the second measurement and nausea across both measurements (p = 0.004 and p = 0.017), indicating that younger patients reported higher symptom intensity. Logistic regression indicated that employment/housework was primarily linked to the total symptom score in Measurement A (p = 0.010), with patients less likely to have high symptom severity (Exp(B) = 0.101). Baseline symptom burden category at Measurement A was identified as a significant predictor of symptom intensity at Measurement B (p = 0.028), with patients presenting mild symptom burden at baseline being less likely to report moderate-to-high symptom burden at the final assessment. Conclusions: While pain, fatigue, and perceived well-being deteriorated from the early to the final chemotherapy cycle, the total symptom burden remained relatively stable. Younger patients appeared to experience higher symptom burden, while lower educational level was associated with higher symptom burden in the univariate analysis at the final assessment, highlighting the need for age-sensitive and educationally tailored nursing interventions to enhance symptom management in oncology settings.